Vaccines against COVID-19: Relationship between vaccination coverage and new cases of the disease in the Amazon (Research, Society and Development, 2022)
SARS-CoV-2 is a virus from the coronavirus family, first identified in the province of Wuhan, China, on December 31, 2019. In Brazil, the first case of COVID-19 was confirmed on February 26, 2020 in Sao Paulo. It is important to observe and detail the vaccination coverage in different age groups. The general objective of the article is to evaluate the vaccination coverage against COVID-19 in the State of Amazonas, and in parallel, to analyze willingness or hesitation to vaccination, as well as the positive and negative points expected by the populations studied in relation to the vaccine. Analytical observational design study, using the combination of keywords "COVID-19 vaccines AND Vaccination coverage AND Vaccination refusal" in PubMed and Scielo search engines, during the period 2021 and 2022. Thirteen articles were found that were included in the work after the selection, in addition to the creation of 13 bulletins. The articles found addressed different populations and their tendencies to vaccinate or not, specifying the factors that people considered favorable or unfavorable to vaccinate. The main fears of the population about the vaccine are its adverse reactions and its effectiveness. It is fundamental to organize events planned for the vaccination process, promoted by the State responsible for the health of the population, as well as, it is also its responsibility to ensure, in an understandable and adequate way for people, the benefits of being vaccinated against COVID-19.